I remember being nice: self-enhancement memory bias in middle childhood. Issue 2 (7th February 2021) - Rowell, Shaina F.; Jaswal, Vikram K.
ABSTRACT: Adults tend to remember themselves in a positive way. For example, they are more likely to remember their past good deeds rather than their past bad deeds. We investigated whether children ( N = 40) are also biased in how they remember information related to themselves. Using the self-reference memory paradigm, we found that 8- to 10-year-olds' source memory for mean action phrases (e.g., "Lie to someone") was worse when the phrases were encoded with reference to themselves compared to when they were encoded with reference to others. Source memory for self-referenced mean phrases was also worse than source memory for self-referenced nice action phrases (e.g., "Be kind to someone") and self-referenced neutral action phrases (e.g., "Draw a circle"). These results provide some of the first experimental evidence for self-enhancement in children's memory.